The "In crowd" and social cruelty - Thompson, Michael, 1947-; Stossel, John.; ABC News.; ABC News Productions ([New York] : ABC News Productions, 2007)
What does it take to be popular? John Stossel discovers why kids dish it out, why they take it and what schools can do to make it better. Guests include psychologist Michael Thompson, author of 'Best Friends, Worst Enemies'. Stossel also visits schools with successful anti-bullying programs.
Title from container.
Originally broadcast as a segment of the television program 20/20 in 2002.
DVD format.
Correspondent: John Stossel .
Keywords: Peer pressure in adolescence; Bullying in schools -- Prevention; School children -- Conduct of life; Cliques (Sociology)